Potential of Beluntas Leaf Extract (Pluchea indica L) as a basic ingredient for Making Liquid Anti-Mosquito Repellent - Sitti Rahmawati; Winarsih; Tri Santoso; Dewi Satria Ahmar; Magfirah; Suherman (Postgraduate, University of Mataram, 2024)
The herbaceous Belugas leaves (Pluchea indica L.) belong to the Asteraceae family and are commonly utilized as food and hedges. They typically grow wild. Alkaloids, saponins, flavonoids, tannins, triterpenes, and steroids are among the substances found in belugas leaves that may have insecticidal properties. The purpose of this study is to use the leaf extract of Beluntas (Pluchea indica L.) as a foundational component for liquid mosquito repellant. In order to produce a thick extract of beluntas leaves, this study used an extraction process that involved evaporating 96% ethanol solvent. Several concentrations of the thick extract were diluted, including 15%, 25%, 35%, 45%, and 55%. The collected data, which was mosquito mortality, was subjected to a One-Way Anova test with a significance level of p = 0.000 <0.05, and then the Duncan test. The findings demonstrated that the number of mosquitoes that perished varied depending on the concentration fluctuations of beluntas leaf extract, with the highest concentration of beluntas leaf extract killing mosquitoes at a rate of 55% and a mosquito mortality percentage of 98.4%.